Pengembangan Media Pembelajaran Berbasis E-Flipbook Dengan Pendekatan Kontesktual Pada Teks Puisi Di Uptd SMP Negeri 7 Gunungsitoli - Bate’e, Krisnawati; Halawa, Noibe; Ndruru, Mastawati; Harefa, Noveri Amal Jaya (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop e-flipbook-based learning media with a contextual approach in learning poetry texts at UPTD SMP Negeri 7 Gunungsitoli. The background of this study is based on the low interest and understanding of students in poetry caused by conventional learning methods that tend to be monotonous and less interesting. This study examines the process of media development, feasibility, practicality, and effectiveness of e-flipbooks as learning media. The development of this media uses the Research and Development (R&D) method with the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. The results of the study indicate that the e-flipbook-based Learning Media with a contextual approach has very good feasibility based on validation from three experts: material experts reaching (99%), language experts reaching (96%), and design experts reaching (95%). The practicality of the developed media was assessed through student response questionnaires in small group trials reaching (90%) which shows that this media is very practical to use in learning. The effectiveness of the developed media was measured by the results of student learning tests, which showed a percentage completion of 100% with an average value of 93, which met the Learning Objective Achievement Criteria (KKTP). Based on these results, it can be concluded that e-flipbook-based learning media with a contextual approach is feasible, practical and effective for learning poetry text material at UPTD SMP Negeri 7 Gunungsitoli.